2018
DOI: 10.2147/ijn.s149375
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive visualization of early osteoarthritic cartilage using targeted nanosomes in a destabilization of the medial meniscus mouse model

Abstract: Background Early stage osteoarthritis (OA) is clinically asymptomatic due to the avascular and the aneural nature of the cartilage tissue. Nevertheless, early detection of cartilage tissue is critical in order to impede the progression of OA. Hence, in order to develop effective preventive therapy for OA, diagnosis in the early stages is necessary. Methods To achieve this goal, we have developed targeted, fluorescent nanosomes conjugated with monoclonal anti-type II col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…After intravenous injection, these particles migrate into the joint but do not bind to cartilage unless the collagen II network is exposed, namely i n conditions of tissue degradation [91]. Additionally, similar particles were shown via fluorescence to accumulate in the knee in a manner proportional to OA severity in vivo [92].…”
Section: Active Targeting To Cartilagementioning
confidence: 99%
“…After intravenous injection, these particles migrate into the joint but do not bind to cartilage unless the collagen II network is exposed, namely i n conditions of tissue degradation [91]. Additionally, similar particles were shown via fluorescence to accumulate in the knee in a manner proportional to OA severity in vivo [92].…”
Section: Active Targeting To Cartilagementioning
confidence: 99%
“…17,18 Targeting strategies for cartilage have leveraged these unique ECM characteristics, including passive targeting of nanomaterials to cartilage via electrostatic attraction to the anionic cartilage matrix 19,20 and active targeting strategies using binding moieties or agents specific to collagen type II. [21][22][23] Synovial fluid, the viscous non-Newtonian fluid within the joint space, is essential not only for shock absorption and lubrication but also for modulating the transport of various molecules to different tissues of the joint. Synovial fluid is a protein-rich mixture of plasma and hyaluronan synthesized by type B fibroblast-like synoviocytes.…”
Section: Anatomy Of a Synovial Jointmentioning
confidence: 99%
“…Moreover, targeting cartilage extracellular matrix (ECM) components such as collagen Type II and aggrecan has gained attention as a promising strategy to target damaged areas of the articular cartilage (Figure 3). In fact, monoclonal anti‐Type II collagen antibodies (MabCII) have been used in multiple drug delivery and diagnostics applications 97‐99 . For example, Cho et al demonstrated that liposomes functionalized with a collagen Type II monoclonal antibody are able to bind cartilage tissue proportionally to the severity of the disease in a mice model of OA after systemic administration 99 .…”
Section: Targeting For Ia Drug Deliverymentioning
confidence: 99%
“…In fact, monoclonal anti‐Type II collagen antibodies (MabCII) have been used in multiple drug delivery and diagnostics applications 97‐99 . For example, Cho et al demonstrated that liposomes functionalized with a collagen Type II monoclonal antibody are able to bind cartilage tissue proportionally to the severity of the disease in a mice model of OA after systemic administration 99 . Moreover, Bedingfield et al used MabCII‐functionalized polymeric NPs for cartilage‐specific MMP13 siRNA delivery.…”
Section: Targeting For Ia Drug Deliverymentioning
confidence: 99%